Effect of keratometric astigmatism on visual outcomes following small incision lenticule extraction - Liu, Shengtao; Yu, Lanhui; Lu, Zhiyuan; Cheng, Chiwen; Gu, Xuejun; Liu, Jingying; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose: To investigate the influence of keratometric astigmatism on visual outcomes following small incision lenticule extraction (SMILE). Methods: Eighty eyes undergoing SMILE for myopia correction were classified into two groups based on preoperative keratometric astigmatism: low keratometric astigmatism (LA) and high keratometric astigmatism (HA) groups. Refractive outcomes, vector components, and changes in higher order aberrations (HOAs) were evaluated preoperatively and 6 months postoperatively. Results: At the postoperative 6-month visit, no significant difference was observed in the decentered distance between the HA and LA groups (HA: 0.17 ± 0.08 mm, LA: 0.16 ± 0.08 mm, P = 0.189). No significant differences in the correction index (P = 0.481), absolute angle of error (P = 0.104), or index of success (P = 0.147) were observed between the two groups. There was no significant difference in the induction of corneal aberrations between the two groups. Furthermore, there were no significant associations between the decentered distance and the vector components of astigmatic correction or induction of higher-order aberration in the HA group (P ≥ 0.294, P ≥ 0.112) or the LA group (P ≥ 0.323, P ≥ 0.080). Conclusions: SMILE for high keratometric astigmatism could achieve comparable treatment centration and visual quality to that of low keratometric astigmatism.